Determination of some metals contained in well drinking water obtained from some secondary schools in Sokoto East District, Nigeria - Sarkingobir, Yusuf; Hiliya, Abbas Abubakar; Miya, Yusuf Yahaya; Umar, AI; Yabo, Aminu Musa; Salah, Nura Maiakwai (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
This study determined the levels of metals (calcium, magnesium, potassium, cadmium, chromium, lead, copper, zinc, and iron) in well water obtained from three secondary schools in Sokoto East district, Nigeria. Standard methods, procedures, and analytical grade reagents were used to determine the metals in atomic absorption spectroscopy. The results were expressed using calculated mean and standard deviation and tested using one-way analysis of variance (ANOVA) and found to be significant . The ranges of determined potassium, calcium, and magnesium are ppm, ppm, and ppm respectively; the ranges of zinc, copper, and iron are: ppm, ppm, and ppm respectively; and the ranges of determined cadmium, chromium, and lead are: ppm, ppm, and ppm respectively. Thus, the water contains heavy metals that can elicit adverse effects on school-aged children, especially chronic exposure; therefore, treated drinking water should be provided to safeguard the health and academic capacity of students and other school actors. Penelitian ini bertujuan untuk menentukan kadar logam (kalsium, magnesium, kalium, kadmium, kromium, timbal, tembaga, seng, dan besi) dalam air sumur yang diperoleh dari tiga sekolah menengah di distrik Sokoto East, Nigeria. Metode standar, prosedur, dan reagen kelas analitik digunakan untuk menentukan logam dalam spektroskopi serapan atom. Hasilnya dinyatakan dengan menggunakan rata-rata yang dihitung dan standar deviasi dan diuji menggunakan analisis varians satu arah (ANOVA) dan ditemukan signifikan . Kandungan kalium, kalsium, dan magnesium yang ditentukan masing-masing adalah ppm, ppm, dan ppm; kisaran seng, tembaga, dan besi masing-masing adalah: ppm, ppm, dan ppm; dan rentang kadmium, kromium, dan timbal yang ditentukan adalah: ppm, ppm, dan ppm. Dengan demikian, air tersebut mengandung logam berat yang dapat menimbulkan efek buruk pada anak usia sekolah, terutama paparan kronis; oleh karena itu, air minum olahan harus disediakan untuk menjaga kesehatan dan kapasitas akademik siswa dan pelaku sekolah lainnya.